Trend and Causative Factors of Road Traffic Crashes in Nigeria: A Six Sigma (DMAIC) Approach - Oliver Ibor Inah; Michael Ikpi Ofem; Fidelis Ibiang Abam; Samuel Oliver Effiom; Omini Okon Jimmy (Journal of Road Safety)
In Nigeria, Road Traffic Crashes (RTC) are a major health problem that result in numerous deaths and financial losses. Thus, it is important to monitor the existing road safety policies and continue further steps to prevent RTC. This study used the Define, Measure, Analyse, Improve, and Control (DMAIC) approach of Six Sigma to investigate the trends and causative factors of RTC in south-south and southeast regions in Nigeria between 2020 and 2023. The findings reveal that the south-south region experienced a higher number of total RTC including a higher proportion of crashes resulting in death (17.5%) compared to the southeast region (14.4%). The majority of crashes in both regions resulted in a serious injury outcome (south-south region, n=6,281, 82.5%; southeast region, n=6,529, 85.6%). Study findings indicated that the mortality, human damage, and case fatality rates were statistically significant between the two regions, with the south-south region facing more severe consequences of each. Overall, the causative-effects analysis showed that speeding violations was the primary contributors to RTC in both the regions. Short and long-term measures for improvement to prevent RTC are included.